Strengthening higher education for a successful workforce - Shuib, Munir (IIUM Press, 2009)
Strengthening Higher Education for a Successful Workforce is a timely collection of thought-provoking articles designed for educators, administrators and policy makers in higher education in determining the direction to set in the future with regards to producing a successful workforce. It also seeks to complement the existing discussion on HE-related issues particularly the ones that emphasize on unemployment among HLI graduates. The book features in-depth discourses by academic members of different disciplines, who present their critical views and research findings, discuss pertinent issues and challenges and identify strategies to strengthen the higher education sector. Strengthening Higher Education for a Successful Workforce is especially recommended for educators and administrators seeking to chart a successful future for the students in their HLI and ultimately for their nation.